2015
DOI: 10.1093/mnras/stv1767
|View full text |Cite
|
Sign up to set email alerts
|

An H i view of galaxy conformity: H i-rich environment around H i-excess galaxies

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…Here we have been considering possible scenarios that can explain their H i gas content. H i-rich central galaxies could be a result of H i-rich mergers and/or gas accretion from the intrafilament medium (Janowiecki et al 2017;Kleiner et al 2017;Wang et al 2015). However, gas accretion from minor mergers is thought not to be significant, Sancisi et al (2008) and Di Teodoro & Fraternali (2014) estimate (for spiral galaxies from the WHISP sample) a maximum gas accretion rate to be 0.1-0.2 and 0.28 M yr −1 respectively, which is not enough to sustain star formation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have been considering possible scenarios that can explain their H i gas content. H i-rich central galaxies could be a result of H i-rich mergers and/or gas accretion from the intrafilament medium (Janowiecki et al 2017;Kleiner et al 2017;Wang et al 2015). However, gas accretion from minor mergers is thought not to be significant, Sancisi et al (2008) and Di Teodoro & Fraternali (2014) estimate (for spiral galaxies from the WHISP sample) a maximum gas accretion rate to be 0.1-0.2 and 0.28 M yr −1 respectively, which is not enough to sustain star formation.…”
Section: Discussionmentioning
confidence: 99%
“…The less massive galaxies have smaller gravitational potentials and no evidence of cold gas accretion from the large-scale structure is observed. Wang et al (2015) show H i-rich galaxies are surrounded by a H i-rich environment where the gas is situated in clumps, hosted by small satellite galaxies or density peaks in the diffuse H i intergalactic medium. These observations also support the CWD model and are best explained by cold mode accretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the quenching (i.e., the cessation of star forming activities in galaxies) properties of central galaxies, such as star formation rate (SFR), morphology, neutral hydrogen content, and broad-band colour, are correlated with those of their neighbouring galaxies (Weinmann et al 2006;Yang et al 2006;Ann et al 2008;Kauffmann et al 2010;Prescott et al 2011;Kauffmann et al 2013;Knobel et al 2015;Hartley et al 2015;Wang et al 2015;Kawinwanichakij et al 2016;Berti et al 2017). This socalled "galactic conformity" phenomenon exists over two distinct distance scales between the central galaxy of a primary dark matter halo and its surrounding galaxies, including the true satellite galaxies within the same halo (<0.5 h −1 Mpc; E-mail: zu.4@osu.edu first detected by Weinmann et al 2006) 1 , and galaxies in halos that are a few virial radii away from the primary (∼3 h −1 Mpc) -effects we refer to as "1-halo" and "2-halo" conformities, respectively.…”
Section: Introductionmentioning
confidence: 99%